Digital Learning of English: EFL Learners’ Perceptions and Teaching Activities - Rida Maisani; Tahrun Tahrun; Mulyadi Mulyadi (Universitas Pahlawan Tuanku Tambusai, 2022)
Digital learning is one way to overcome learning during a pandemic. There are several platforms that teachers can use in carrying out learning such as WhatsApp, YouTube and Google Classroom. This mixed method research aims to find out how were the teachers’ implementation of digital learning and how were EFL learners’ perception on teaching activities through digital learning of English. This research was conduct at Senior High School YPI Tunas Bangsa of Palembang. There were several samples including principal, one English teachers and eighty students’. The data obtained from interview, questionnaire, and documentation. Analyzed by using data reduction, data display and conclusion. The results showed that the implementation of platform and the students’ perception of learning English through digital technology. This research is expected to be one of the solutions to improve the way teachers implement learning through student perceptions.